An exploratory study of creativity, personality and schooling achievement. Issue 5 (2nd September 2016) - Berlin, Noémi; Tavani, Jean-Louis; Beasançon, Maud
ABSTRACT: We investigate the link between schooling achievement and creativity scores, controlling for personality traits and other individual characteristics. Our study is based on field data collected in a secondary school situated in a Parisian suburb. Four scores of creativity were measured on 9th graders. Verbal divergent thinking negatively predicts the grades in most subjects, but graphical integrative thinking is positively correlated with scientific grades. There is no significant correlation with the other measures of creativity, implying a low importance of creativity in school. In line with previous work, we find that conscientiousness and openness are positively associated with grades.